Processes and partnerships for effective regional surveillance of banana diseases - Beed, Fenton D.; Kubiriba, Jerome; Mugalula, A.; Kolowa, H.; Bulili, S.; Nduwayezu, A.; Murekezi, C.; Sakayoya, E.; Ndayihanzamaso, P.; Mulenga, R.; Abass, A.; Mathe, L.; et al. (CAB International, 2013)
Crop diseases do not respect country borders and yet preventive measures to curtail the introduction, establishment and spread of diseases are often coordinated on a country-by-country basis. This is because each country has its own mandate to safeguard food security and trade relations. However, knowledge held by researchers and regulatory officials within each country for any given disease can benefit those in neighbouring countries, and this can be reciprocated for other diseases, depending on aggregated disease distribution and experience of methods for effective diagnosis and management. Based on an appreciation of this common goal, national research and regulatory officials from seven countries networked to prioritize which diseases of banana (Musa spp.) were of critical importance and where to undertake spatially designed surveillance exercises around the Great Lakes region of sub-Saharan Africa. Surveys for banana Xanthomonas wilt and banana bunchy top disease were targeted to zones where outbreaks had been reported but not confirmed, and where invasion risk was high as a consequence of proximity to areas or countries known to contain either disease. To ensure that disease diagnoses were precise, field based visual assessments of symptoms were supported by molecular based diagnostics performed under laboratory conditions. Samples were transferred from plants in the field to the laboratory using pathogen DNA capture kits that could be swiftly and safely moved across country borders for analysis at a centralized laboratory to ensure that results from different surveys could be compared. The accuracy of global positioning system (GPS) coordinates recorded as the origin of samples from surveys was validated by comparing the altitude given by the GPS with altitude data provided by digital elevation models. Geographical information system (GIS) maps could then be generated to clearly show the prevalence of banana Xanthomonas wilt and banana bunchy top disease for the zones surveyed. Furthermore, the GIS maps can be used to interpolate different GPS-linked data sets to highlight factors driving disease establishment and spread, such as conducive environmental conditions, and to determine where to prioritize management strategies based on food insecurity measures. The need to prioritize investments across a region is of particular importance in developing countries where capacities for disease surveillance and diagnostics are limited, resulting in inaccurate pest lists and, as a consequence, limited prospects for sustained agricultural trade. If there is political will for regional communication, harmonized diagnostics and reporting mechanisms, the current scenario of fighting fully blown epidemics with exorbitant funds can be averted by coordinated, pre-emptive and thus cost efficient management interventions.